The argonauts - Nelson, Maggie, 1973- (Minneapolis, Minnesota : Graywolf Press, 2016)
"A genre-bending memoir, a work of 'autotheory' offering fresh, fierce, and timely thinking about desire, identity, and the limitations and possibilities of love and language. It binds an account of Nelson's relationship with her fluidly gendered partner and a journey to and through a pregnancy to a rigorous exploration of sexuality, gender and family."--Cover.
National Book Critics Circle Award for Criticism, 2015.
boek
Keywords: Sexual minorities' families; Families; Sexual minorities' families